Sports in Nigeria: going round in circles (Lagos, Nigeria International Tennis Academy Press, 2022)
The author brings to bear his work as a tennis developer, sports promoter, and marketer in his writing
osc 30/11/22
Loans
Keywords: Sports - administration; Nigeria